2007
DOI: 10.1158/0008-5472.can-06-2783
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics-Based Identification of Proteins Secreted in Apical Surface Fluid of Squamous Metaplastic Human Tracheobronchial Epithelial Cells Cultured by Three-Dimensional Organotypic Air-Liquid Interface Method

Abstract: Squamous cell carcinoma in the lung originates from bronchial epithelial cells that acquire increasingly abnormal phenotypes. Currently, no known biomarkers are clinically efficient for the early detection of premalignant lesions and lung cancer. We sought to identify secreted molecules produced from squamous bronchial epithelial cells cultured with organotypic culture methods. We analyzed protein expression patterns in the apical surface fluid (ASF) from aberrantly differentiated squamous metaplastic normal h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 46 publications
0
29
0
Order By: Relevance
“…Other works have recently described nuclear–cytoplasmic positive staining of serpin (maspin and SCCA) in non-small cell lung carcinoma. In this work, the nuclear maspin positivity was correlated with a better survival than with cytoplasmic staining 32. The synthesis of SCCA is thought to be essentially in the cytoplasm.…”
Section: Discussionmentioning
confidence: 56%
“…Other works have recently described nuclear–cytoplasmic positive staining of serpin (maspin and SCCA) in non-small cell lung carcinoma. In this work, the nuclear maspin positivity was correlated with a better survival than with cytoplasmic staining 32. The synthesis of SCCA is thought to be essentially in the cytoplasm.…”
Section: Discussionmentioning
confidence: 56%
“…Cells were cultured in RPMI containing 10% FBS. Normal human tracheobronchial epithelial (NHTBE) cells (Clonetics, San Diego, CA), which were used as the control, were cultured by a three-dimensional organotypic air-liquid interface method as described previously (31)(32)(33)(34)(35). Ro-31-8220 was purchased from Calbiochem (La Jolla, CA) and prepared in DMSO.…”
Section: Cell Culturementioning
confidence: 99%
“…Analysis and identification of proteins in secretomes using proteomics . Tissue SCC antigen 1 and 2 [105] Sardana et al Tissue Not reported in this study [108] Pardo Tissue serpins [110] Chevallet et al Serum, tissue Dihydrodiol dehydrogenase [98] Chen et al…”
Section: Enrichment Of Low-abundant Tissue Proteins In Body Fluids Bymentioning
confidence: 78%
“…This new source is being increasingly interrogated by the clinical proteomics community, as is Biomarkers Med. (2007) 1(4) future science group future science group apparent from the rapid rise in publications: a PubMed search using various combinations of the keywords 'secretome' or 'cell-conditioned medium' and 'proteomics' or 'mass spectrometry' yielded two primary papers in 2004 [88,89], four papers in 2005 [90][91][92][93], six papers in 2006 [94][95][96][97][98][99] and already ten papers mid-2007 [100][101][102][103][104][105][106][107][108][109][110]. Importantly, half of the studies (11) describe differential analyses between cancer cell types or stages and have validated selected secretome candidates in patient material using antibodybased assays in serum or tissue microarrays.…”
Section: Enrichment Of Low-abundant Tissue Proteins In Body Fluids Bymentioning
confidence: 99%
See 1 more Smart Citation